Correlation of the morphology and thermooxidative degradation behavior of poly(ethylene terephthalate)–nitrile butadiene rubber–polycarbonate ternary blends. Issue 10 (30th October 2018) - Ali‐Asgari Dehaghi, Hamidreza; Boudaghi Malidareh, Amin; Edraki, Milad; Sedaghat, Navid; Farokhzad, Ardalan
Abstract: In this study, we prepared ternary poly(ethylene terephthalate) (PET)–nitrile butadiene rubber (NBR)–polycarbonate (PC) blends through a molten mixing procedure, and with a corotating extruder, we studied the morphology and thermodynamic properties of each purified polymer and the binary and ternary blends with different compositions. Dynamic mechanical analysis of both the PET–PC and PET–NBR samples showed individual loss peaks for each component, but in different ternary samples, the effects of different percentages of components (PC–PC and PET–NBR) were observed; this revealed changes in the loss peak locations. Individual loss peaks of PET and PC in the ternary PET–NBR–PC blends (81/9/10 and 63/30/7)—proof of the miscibility of the samples—were also observed in this study. The thermal properties of the samples were measured and examined with the thermogravimetric analysis and differential thermogravimetry testing methods. The activation energy and order of reaction values for the samples under an air atmosphere with single‐rate methods of heating were studied. Finally, the relation between the type of morphology and the thermal degradation behavior was investigated. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47171. Abstract :